2018
DOI: 10.18502/kls.v4i4.2273
|View full text |Cite
|
Sign up to set email alerts
|

Climate Factors and Dengue Fever in Jakarta 2011–2015

Abstract: Dengue fever is a public concern because of its outbreak with a high mortality rate.Aedes aegypti as a vector of dengue fever is very sensitive to its environment, especially to climate variability. The aim of the study was to examine the correlation between climate factors (temperature, rainfall, humidity, and solar radiation) and dengue fever cases in Jakarta 2011-2015, since Jakarta is the capital city of Indonesia.It was a quantitative study with an ecological study design. A correlation test was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Solar radiation has a negative impact (− 0.0001), which is consistent with Ekasari et al ( 2018 ), Jaya and Folmer ( 2021a ) and Martínez-Bello et al ( 2017b ). An increase of 1 kJ m −2 day −1 of solar radiation decreases the relative dengue risk by .…”
Section: Application: Relative Dengue Risk At Subdistrict Level In Ba...supporting
confidence: 87%
See 1 more Smart Citation
“…Solar radiation has a negative impact (− 0.0001), which is consistent with Ekasari et al ( 2018 ), Jaya and Folmer ( 2021a ) and Martínez-Bello et al ( 2017b ). An increase of 1 kJ m −2 day −1 of solar radiation decreases the relative dengue risk by .…”
Section: Application: Relative Dengue Risk At Subdistrict Level In Ba...supporting
confidence: 87%
“…As shown by Rasjid et al ( 2019 ), strong solar radiation negatively influences the breeding and spread of Aedes-spp mosquitoes. A longer spell of solar radiation implies a shortened spell of dawn and dusk, during which the Aedes-spp mosquito preys on animals and humans, particularly 20 to 30 min after sunset (Ekasari et al 2018 ; Jaya and Folmer 2021a ).…”
Section: Application: Relative Dengue Risk At Subdistrict Level In Ba...mentioning
confidence: 99%
“…The study found that minimum temperatures showed a strong correlation with dengue incidence from January to March, but closer to the beginning of the dengue season, from April to June, there was a negative correlation. Ekasari, in their study between 2011 and 2015, found the highest number of dengue incidences in April 2014 and the lowest in October 2012, which associates with the wet and dry seasons of the country [ 24 ]. Finally, the surge in the Aedes population is connected with an increase in temperature, relative humidity, and precipitation during the monsoon season, which is followed by an increase in the prevalence of dengue [ 25 ].…”
Section: Introductionmentioning
confidence: 99%